An intelligent vehicle management system for reducing greenhouse gas emission – a case study of hybrid vehicle engine. (1st January 2012) - Wong, David W.C.; Choy, K.L.; Lam, H.Y.; Lin, Canhong; Lee, Carmen K.H.; Chow, Harry K.H.; Zhang, Xiaodong
In this paper, a genetic algorithm based vehicle management system is proposed to determine 'green' components of a new vehicle engine so as to reduce the greenhouse gases emission level. The proposed system is developed using genetic algorithm (GA) to define the appropriate sets of components for the development of vehicle engine. The novel idea of this paper is to develop a system that considers the transport system infrastructure as one of the important factor for the design of vehicle engine system. The proposed system is applicable for the vehicle engine development into the current hybrid electric vehicle. A case study is conducted to illustrate the functionality of the proposed system, the scenario study and operations procedures of GA are also discussed in the case study. Finally, results from the simulation highlight the value of this system toward the reduction of the fuel consumption and pollutants.